Validity of Adenosine Deaminase (ADA) Level in Pleural Fluid for the Diagnosis of Tuberculosis - Abdul Wahid, Afia Haque, Mohammad Azam, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The pleural fluid LDH/ADA ratio, which can be determined from routine biochemical analysis, is highly predictive of TPE at a cut-off level of 16.20. Measurement of this parameter may be helpful for clinicians in distinguishing between TPE and PPE. Despite wide variations in the reported sensitivity and specificity of pleural fluid ADA level, it can be used as a surrogate for pleural biopsy when the latter is not feasible. Adenosine deaminase (ADA) is the most cost-effective pleural fluid marker and is routinely used in high prevalence settings, whereas its value is questioned in areas with low prevalence. The lymphocyte proportion (LP) is known to increase the specificity of ADA for this diagnosis. Objectives: To determine the diagnostic accuracy of ADA level in pleural fluid for the diagnosis of TB as compared to other conventional methods available like gene expert. Materials & Methods: The design of this study was a cross sectional study design. This study was conducted in Medicine Unit III, S.P.H. Quetta and the duration of this study was from 23rd October 2019 to 22nd April 2020. A total of 423 patients with pulmonary TB between the ages of 25 years to 45 years, having developed pleural effusion were included. Patients with pleural effusion due to causes other than TB, having extra pulmonary TB and those with other respiratory infections were excluded. Tests done specifically for TB in our setup include sputum AFB, CXR, and genexpert. These patients’ pleural fluid ADA were then sent. Results: Adenosine deaminase (ADA) found that 217 were True Positive and 13 were False Positive. Among 193, adenosine deaminase (ADA) negative patients, 12 (False Negative) had TB on gene expert whereas 181 (True Negative) had no TB on gene expert (p=0.0001). Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of ADA level in pleural fluid for the diagnosis of TB as compared to other conventional methods available like gene expert was 94.76%, 93.30%, 94.35%, 93.78% and 94.09% respectively. Practical Implication: This study was conducted to determine the validity of ADA levels for the diagnosis of TB and the results of this study if favorable will decrease the need for other laboratory tests usually done which take longer time, thus helping to decrease the need for multiple tests, early availability of report and timely management of the disease. This will further help to reduce the contact rate of TB and the risk of developing MDR TB by starting early treatment. Conclusion: This study concluded that diagnostic accuracy of ADA level in pleural fluid for the diagnosis of TB is quite high. Keywords: Pulmonary Tuberculosis, Pleural Fluid, Adenosine Deaminase, Biochemical, Mycobacterium .